The influence of transparency and disclosure on the valuation of banks in India: The moderating effect of environmental, social, and governance variables, shareholder activism, and market power - Venkata Mrudula Bhimavarapu; Shailesh Rastogi; Rebecca Abraham (Journal of Risk and Financial Management, 2022)
Research on the impact of transparency and disclosures (TD) on the firm's valuation presents an ambiguous result. The effect of disclosure on value is a concern because disclosure is not an economic activity. It grows further due to the embellishment of positive disclosures and the suppression of hostile facts. This situation has motivated the authors to conduct the current research. The study aims to empirically find the influence of TD on the valuation of banks in India while the Environmental, Social, and Governance Index (esgi), Shareholder activism index (shai), and Lerner Index (li) act as moderators. A panel data regression (PDR) is adopted to analyse the data in the study. Panel data for 31 public/private banks for ten years (2010-2019) are collated. The authors used econometric models to understand the linear, quadratic, and interaction association of Transparency and Disclosure (TD) with the valuation of the banks in India. It is empirically found that TD alone does not impact the valuation of banks but is positively associated with a bank's value under the influence of the moderators, Environmental, Social, and Governance variables (esgi), and shareholder activism (shai).
Keywords: 650; banks; transparency; disclosures; Lerner Index; valuation